Adult tonsillectomy: postoperative pain depends on indications - Zagólski,Olaf (2016)
ABSTRACT INTRODUCTION: Intense pain is one of the most important postoperative complaints after tonsillectomy. It is often described by patients as comparable to the pain that accompanies an acute tonsillitis. Although recurrent tonsillitis is the most frequent indication for surgery, many tonsillectomies are performed due to other indications and these patients may be unfamiliar with such pain. OBJECTIVE: To verify whether individuals with recurrent tonsillitis experience different post-tonsillectomy pain intensity than those with other indications for surgery, with no history of episodes of acute tonsillitis. METHODS: A total of 61 tonsillectomies were performed under general anesthesia, using a potassium titanyl phosphate (KTP) laser (to eliminate the potential influence on the study results of forceful dissection of fibrotic tonsils in patients with history of recurrent tonsillitis) and multiple ligations of blood vessels within the tonsillar beds. The patients received 37.5 mg Tramadoli hydrochloridum + 325 mg Paracetamol tablets for 10 days. Postoperative variables included the duration of hospital stay, postoperative hemorrhage and readmission rate. The patients reported pain intensity on consecutive days, pain duration, weight loss on postoperative day 10, character, intensity and duration of swallowing difficulties, and the need for additional doses of painkillers. Healing was also assessed. Capsular nerve fibers were histologically examined in the resected tonsils by immunostainings for general and sensory markers. RESULTS: Indications for the surgery were: recurrent acute tonsillitis (34 patients), no history of recurrent tonsillitis: focus tonsil (20) and intense malodour (7). Pain intensity on postoperative days 3-4 and incidence of readmissions due to dehydration were significantly higher in the group with no history of recurrent tonsillitis. No significant differences in relative densities of protein gene product (PGP) 9.5- and calcitonin gene-related peptide (CGRP)-immunoreactive nerve fibers were observed. CONCLUSION: Patients with recurrent tonsillitis qualified for tonsillectomy reported lower pain intensity than those without recurrent tonsillitis and the pain scores were unrelated to nerve fibers density.